2012
DOI: 10.1007/s10493-012-9633-y
|View full text |Cite
|
Sign up to set email alerts
|

Wheat curl mite, Aceria tosichella, and transmitted viruses: an expanding pest complex affecting cereal crops

Abstract: The wheat curl mite (WCM), Aceria tosichella, and the plant viruses it transmits represent an invasive mite-virus complex that has affected cereal crops worldwide. The main damage caused by WCM comes from its ability to transmit and spread multiple damaging viruses to cereal crops, with Wheat streak mosaic virus (WSMV) and Wheat mosaic virus (WMoV) being the most important. Although WCM and transmitted viruses have been of concern to cereal growers and researchers for at least six decades, they continue to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 148 publications
2
119
0
1
Order By: Relevance
“…data), on human travelers, or by taking advantage of past and present military conflicts, using the movement of the war logistical resources to extend their range to other countries and continents (Lockwood 2009;Canyon et al 2011;Pimentel 2011;Chevillon et al 2012). The economic or medical importance of the Acari increases with their ability to vector viruses, rickettsiae, spirochaetes, phytoplasmas, mycoplasmas and protozoas, or to harbor and transport nematodes, bacteria and fungi pathogens that affect plants, domestic and wild animals and humans (Jongejan and Uilenberg 2004;Mullen and OConnor 2009;Nicholson et al 2009;Bastianel et al 2010;Navajas et al 2010;Navia et al 2010Navia et al , 2012aRodrigues and Childers 2012).…”
Section: The Voyage Of Adventive and Invasive Acarimentioning
confidence: 99%
See 1 more Smart Citation
“…data), on human travelers, or by taking advantage of past and present military conflicts, using the movement of the war logistical resources to extend their range to other countries and continents (Lockwood 2009;Canyon et al 2011;Pimentel 2011;Chevillon et al 2012). The economic or medical importance of the Acari increases with their ability to vector viruses, rickettsiae, spirochaetes, phytoplasmas, mycoplasmas and protozoas, or to harbor and transport nematodes, bacteria and fungi pathogens that affect plants, domestic and wild animals and humans (Jongejan and Uilenberg 2004;Mullen and OConnor 2009;Nicholson et al 2009;Bastianel et al 2010;Navajas et al 2010;Navia et al 2010Navia et al , 2012aRodrigues and Childers 2012).…”
Section: The Voyage Of Adventive and Invasive Acarimentioning
confidence: 99%
“…data). Another group of fast-moving, adventive mites are species in the superfamily Eriophyoidea (Navia et al 2010(Navia et al , 2012a. The number of described species of eriophyoid mites is also quickly growing, which will certainly lead to an increase in the number of invasive species.…”
Section: Adventive Species: Friend or Foe?mentioning
confidence: 99%
“…Significant yield losses are associated with WSMV infections (Graybosch et al, 2009) and at least three additional viruses have been reported as being transmitted by the WCM vector (Navia et al, 2013). There is huge interest in deploying multiple effective genes in combination as a means of disease control and improving the durability of resistance (Liu et al, 2011;Heslop-Harrison and Schwarzacher, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…WMoV is transmitted by the eriophyid wheat curl mite Aceria tosichella Keifer (Seifers et al, 1997), which is also the vector for Wheat streak mosaic virus (WSMV, genus Rymovirus, family Potyviridae) (Navia et al, 2013). WSMV and WMoV are often found in mixed infection (Skare et al, 2006;Navia et al, 2013).…”
Section: Interception Of Wheat Mosaic Virus (Wmov) In Brazil In Maizementioning
confidence: 99%
“…WMoV is transmitted by the eriophyid wheat curl mite Aceria tosichella Keifer (Seifers et al, 1997), which is also the vector for Wheat streak mosaic virus (WSMV, genus Rymovirus, family Potyviridae) (Navia et al, 2013). WSMV and WMoV are often found in mixed infection (Skare et al, 2006;Navia et al, 2013). Until now, there is no report of WMoV in Brazil; however, the recent detection of the pathosystem Aceria tosichella/WSMV in the country (Mar et al, 2013) has alerted to the threat represented by WMoV introduction.…”
Section: Interception Of Wheat Mosaic Virus (Wmov) In Brazil In Maizementioning
confidence: 99%